The Role of Waiters and Waitresses in Supporting Front Office Performance: A Case Study in Five-Star Hotels - Randynata, Ham Beltsazar Kevin; Wijoyo, Tuwuh Adhistyo (International Journal of Integrative Sciences, 2024)
The objective of this study is to examine the crucial contribution of waiters and waitresses in enhancing the performance of the Front Office in the setting of luxury hotels. The study examines the impact of effective communication, mutual support, training programmes, and guest feedback integration on service delivery in two luxury hotels. This is done through qualitative approaches such as semi-structured interviews and participant observation. The results emphasise the significance of establishing effective communication channels to provide prompt information exchange, enabling the Front Office to efficiently anticipate and fulfil guest requirements. Furthermore, the study highlights the importance of interdepartmental collaboration and the influence of comprehensive training programmes in promoting a unified service culture and enhancing guest satisfaction. Incorporating client input into operational operations is a vital factor in achieving ongoing service enhancement and guest loyalty. Potential areas for future research include investigating cutting-edge communication technologies, examining the impact of cultural diversity on collaborative efforts, and utilising emerging technologies in luxury hotel management to enhance service quality to its maximum potential